The Main Factors of Tourism of Thai Tourists Choice to Cultural Travel, to the Mon Community in Lat Krabang District, Bangkok - วุฒิยา, กัญญาพัชร; วัฒนอุดมศิลป์, การสิลักษณ์; โตสัจจะวงษ์, จรูญวิทย์ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This research, entitled the main factors of tourism of thai tourists choice to cultural travel to the mon community in lat drabang district Bangkok aimed to examine the principal tourism factors affecting Thai tourists’ decisions to visit the Mon community in Lat Krabang District, Bangkok.The sample consisted of 400 Thai tourists who visited the Mon community in the specified area. The research instrument was a structured questionnaire, which was validated for content validity by experts and demonstrated a reliability coefficient of 0.809. Data were analyzed using both descriptive and inferential statistics. Descriptive statistics included frequency, percentage, mean, and standard deviation. Inferential statistics involved the use of One-way Analysis of Variance (One-way ANOVA).           The findings revealed that the overall tourism factors were rated at a high level (x̄= 3.96, S.D. = 0.77). Among the three dimensions, Attractions received the highest mean score, followed by Amenities and Accessibility, respectively. Key influential factors included the diversity of tourism activities and attractions, as well as the availability of food and beverage services. Furthermore, the hypothesis testing indicated that differences in monthly income significantly affected opinions regarding Accessibility and Amenities at the 0.05 level of significance, while educational level significantly influenced opinions toward Amenities. The results highlight the importance of cultural identity as a primary driver of tourists’ decision-making, alongside the development of accessible infrastructure and adequate facilities. These findings may serve as empirical evidence to support strategic planning for sustainable community-based tourism development.